DETERMINANTS OF HEALTH PROMOTION FACTORS AMONG ADOLESCENT MOTHERS REGARDING THE RISK OF SOCIO-EMOTIONAL DISORDERS IN TODDLERS - Wida Rahma Arwiyantasari; Mufida Dian Hardika; Nayka Nurrohmah (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Teenage pregnancy is a public health issue that can influence a child's socio-emotional development through biological, psychological, and environmental factors. Health promotion factors during pregnancy are believed to play a role in reducing the risk of socio-emotional disorders; however, evidence regarding mothers with a history of teenage pregnancy remains limited. This study aimed to analyze the determinants of health promotion factors regarding the risk of socio-emotional disorders in children aged 12–59 months. A quantitative approach with a cross-sectional analytic observational design was employed. The sample consisted of 35 mothers who had been pregnant at age ≤19 and currently had children aged 12–59 months, selected using total sampling. Data were collected via questionnaire-based interviews and analyzed using the Chi-square test and multiple logistic regression with IBM SPSS Statistics. Bivariate analysis results indicated that attitude (p=0.048), access to information (p=0.036), and social support (p=0.028) were significantly associated with the risk of socio-emotional disorders in children. Multivariate analysis revealed that social support was the most dominant factor (OR=5.652; 95% CI=1.429–22.354; p=0.014), followed by access to information (OR=4.289; 95% CI=1.158–15.887; p=0.029) and attitude (OR=3.611; 95% CI=1.069–12.195; p=0.039). Knowledge and health promotion activities did not show a significant effect. Social support, access to information, and maternal attitude are key determinants of the risk of socio-emotional disorders in children aged 12–59 months and should therefore be the focus of health promotion efforts.